2021
DOI: 10.3390/ani11061745
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile and Co-Expression Network of Pearl Gentian Grouper under Cold Stress by Integrating Illumina and PacBio Sequences

Abstract: Pearl gentian grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) is a fish of high commercial value in the aquaculture industry in Asia. However, this hybrid fish is not cold-tolerant, and its molecular regulation mechanism underlying cold stress remains largely elusive. This study thus investigated the liver transcriptomic responses of pearl gentian grouper by comparing the gene expression of cold stress groups (20, 15, 12, and 12 °C for 6 h) with that of control group (25 °C) using PacBio SMRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The experimental process (Figure 1A) included temporary fish culture, cold stress treatment, liver tissue collection under anesthesia, and total RNA extraction from samples and was performed following the methods described in our previous transcriptome study (Miao et al, 2021). Briefly, 150 healthy juveniles of the pearl gentian grouper hatched from Hainan (northern South China Sea, China) breeding parents were equally divided into three parallel experimental tanks.…”
Section: Experimental Process and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental process (Figure 1A) included temporary fish culture, cold stress treatment, liver tissue collection under anesthesia, and total RNA extraction from samples and was performed following the methods described in our previous transcriptome study (Miao et al, 2021). Briefly, 150 healthy juveniles of the pearl gentian grouper hatched from Hainan (northern South China Sea, China) breeding parents were equally divided into three parallel experimental tanks.…”
Section: Experimental Process and Sample Collectionmentioning
confidence: 99%
“…This obviously limits the breeding scope and environment of this grouper, which is not conducive to the expansion of its aquaculture industry. For this reason, we previously analyzed changes in the liver transcriptome of pearl gentian grouper under cold stress by integrating PacBio SMRT-Seq and Illumina RNA-Seq technologies and successfully screened various cold-related genes and biological pathways; our results indicated that energy homeostasis may play a crucial role in physiological responses to cold stress in the species (Miao et al, 2021). However, the regulatory relationships and dynamics of these genes are still unclear, and the construction of miRNA-TF-mRNA network is necessary to clarify regulatory mechanisms at the pre-and post-transcriptional levels underlying the transient response to low-temperature stress in this grouper and to narrow the screening of cold-related candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial ribosome-associated GTPase 2 (GTPBP5) plays a role in the regulation of the mitochondrial ribosome assembly and of translational activity, all suggesting the inhibited function of the “cell cycle” and “cell division” [ 49 , 50 , 51 , 52 ]. In the livers of fish, high-temperature stress may affect apoptosis, DNA replication, protein metabolism, energy metabolism, lipid metabolism, immune, cell cycle, protein processing, and transport, as well as antioxidative responses [ 53 , 54 , 55 ], while low-temperature stress may affect signaling transduction, membrane fluidity, lipid metabolism, antioxidative responses, ion binding, macromolecule catabolism, mitochondrial enzymes related to transport, carbohydrate metabolism, and cell cycle endocrine system [ 56 , 57 ]. Interestingly, inositol polyphosphate-5-phosphatase A (INPP5A) and phosphatidylinositol 4,5-bisphosphate 5-phosphatase A (INPP5J) were interlinked as the up- and downregulated DEGs in the network, respectively ( Figure 4 and Figure 5 ), which may suggest the effects of membrane fluidity and lipid metabolism involved in the modulation of inositol function and the influence of cell migration, adhesion, and polarity in P. olivaceus livers under cold shock [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such a strategy may contribute to maintaining contractile function in the trout heart during cold acclimation [ 97 ]. In the pearl gentian grouper, cardiac muscle contraction was detected based on RNA-seq results and could be physiologically adjusted to reduce damage and maintain essential life functions under cold stress [ 98 ]. Herein, we found that the cardiac muscle contraction pathway was significantly enriched in the heart DEGs and that key genes, including cytochrome c oxidase subunit 7A2 gene ( Cox7a2 ) and cytochrome c oxidase subunit 5A gene ( Cox5a ), were upregulated by cold stress.…”
Section: Discussionmentioning
confidence: 99%